2019
DOI: 10.1158/1078-0432.ccr-19-0206
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Starvation and Docetaxel Induce c-Myc–Driven hENT1 Surface Expression to Overcome Gemcitabine Resistance in ASS1-Negative Tumors

Abstract: Purpose: The response to acute and long-term arginine starvation results in a conditional adaptive metabolic reprogramming that can be harnessed for therapeutic opportunities in ASS1-negative tumors. Here, we investigate the underlying biology of priming ASS1 À tumors with arginine deiminase (ADI-PEG20) before treatment with gemcitabine (GEM) and docetaxel (DTX) in sarcoma, pancreatic cancer, and melanoma cell lines.Experimental Design: ASS1 À tumor cell lines were treated to create LTAT (long-term ADI treated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 43 publications
2
47
0
Order By: Relevance
“…Due to the high adaptability of tumor metabolism, most metabolically active drugs are not effective when used as monoagents 15 . However, investigations of the metabolic reprogramming that ASS1-negative tumors undergo as they re-express ASS1 have revealed additional vulnerabilities in ADI-PEG20 sensitive sarcomas 7,8,15,17 . To date, many of these studies have relied upon metabolomic and genetic stratigies to understand the development of resistance to ADI-PEG20 treatment in ASS1 negative tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high adaptability of tumor metabolism, most metabolically active drugs are not effective when used as monoagents 15 . However, investigations of the metabolic reprogramming that ASS1-negative tumors undergo as they re-express ASS1 have revealed additional vulnerabilities in ADI-PEG20 sensitive sarcomas 7,8,15,17 . To date, many of these studies have relied upon metabolomic and genetic stratigies to understand the development of resistance to ADI-PEG20 treatment in ASS1 negative tumors.…”
Section: Introductionmentioning
confidence: 99%
“…6A). Myc is stabilized in SKLMS1 cells upon ADI-PEG20 treatment and the cMyc-Max heterodimerization inhibitor 10058-F4 blocks ADI-driven resistance consistent with this regulatory model (Prudner et al , 2019b). Network analysis indicated that Myc and Max are driven by upstream activation of ERK1/2 (MAPK1/3, Fig.…”
Section: Resultsmentioning
confidence: 61%
“…Many cancers are arginine auxotrophic due to silencing of ASS1 and/or argininosuccinate lyase (Keshet et al , 2018). These tumors are sensitive to ADI-PEG20, which converts arginine to citrulline (Przystal et al , 2018), but ultimately tumors develop resistance through re-expression of ASS1, metabolic reprogramming (Kremer et al , 2017a), and myc stabilization (Prudner et al , 2019b). In order to more broadly understand how cells develop resistance to arginine starvation, we focused on identifying the proteomic adaptations that facilitate metabolic reprogramming, and ultimately escape, in ADI-PEG20 sensitive cells,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations